Dynamics of Salmonella Dublin infection and antimicrobial resistance in a dairy herd endemic to salmonellosis - Victor Santos do Amarante; Joelma Kellen de Castro Pereira; Matheus Ferreira Serafini; Carolina Pantuzza Ramos; Isabela Pádua Zanon; Thayanne Gabryelle Viana de Souza; Tiago Facury Moreira; Antônio Ultimo de Carvalho; Rodrigo Melo Meneses; Flavia Figueira Aburjaile; Vasco Azevedo; Elias Jorge Facury Filho; et al. (PLoS ONE, 2025)
Salmonella Dublin is a serovar that causes severe infections and cattle. Despite the importance of this agent, research on achieving its elimination from dairy farms is limited, which complicates risk mitigation and control efforts. This study thus aimed to assess the prevalence of S. Dublin on a farm with a history of outbreaks, to understand the dynamics of the infection, characterize the antimicrobial resistance of the isolates, and evaluate their genetic similarity. Multiparous cows in the postpartum phase are nearly five times more likely to shed Salmonella sp. A total of 39 cases of fatal septicemic salmonellosis caused by S. Dublin were confirmed in calves aged 3–5 months. Antimicrobial susceptibility was evaluated in 45 strains of S. Dublin, with 48.9% of the isolates classified as multidrug resistant, including resistance to penicillin (48.9%), tetracyclines (42.2%), and fluoroquinolones (33.3%). Seven multidrug-resistant isolates were selected for genomic sequencing. Among the resistance determinants identified, a mutation in the gyrA gene, present in all sequenced isolates, was notable. Analyses of cgMLST and SNPs revealed that the isolates from healthy animals were closely related to those found in animals with confirmed cases of S. Dublin, confirming that the agent was circulating among healthy animals across various categories. A high similarity was also found between the isolates in this study and strains causing salmonellosis in humans in Brazil, thus reinforcing the zoonotic nature and possible epidemiological link between cattle, and the occurrence of this disease in humans.